2003
DOI: 10.1002/eat.10120
|View full text |Cite
|
Sign up to set email alerts
|

Causes and recovery in anorexia nervosa: The patient's perspective

Abstract: Individuals with anorexia nervosa perceive both external (family environment) and personal factors (dieting and stress) as contributory to their disorders. The results underscore the importance of interpersonal factors in recovery from anorexia nervosa and suggest that attention to this area in treatment may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
177
1
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(203 citation statements)
references
References 76 publications
(33 reference statements)
14
177
1
10
Order By: Relevance
“…[30][31][32][33][34] A number of researchers have suggested that a more multidimensional biopsychosocial view of recovery be examined to fully understand the overall effectiveness of treatment and the impact of disease on the patient's life. 9,25,26,35 A small number of studies have taken multidimensional views of AN outcomes. [36][37][38] The purpose of this study was to develop a model of short-term improvement that characterized a minimum set of treatment goals while determining whether RFC on admission predicted improvement over the LOS in residential treatment.…”
Section: Outcomes Of Anorexia Nervosamentioning
confidence: 99%
“…[30][31][32][33][34] A number of researchers have suggested that a more multidimensional biopsychosocial view of recovery be examined to fully understand the overall effectiveness of treatment and the impact of disease on the patient's life. 9,25,26,35 A small number of studies have taken multidimensional views of AN outcomes. [36][37][38] The purpose of this study was to develop a model of short-term improvement that characterized a minimum set of treatment goals while determining whether RFC on admission predicted improvement over the LOS in residential treatment.…”
Section: Outcomes Of Anorexia Nervosamentioning
confidence: 99%
“…[26][27][28][29] Other important factors may include support from family, contact with friends, engagement in activities that help the child focus on something other than the ED, and experiences that improve self-esteem. It is important that those who plan and conduct treatment of young patients with AN know what clients and parents regard as helpful.…”
Section: Introductionmentioning
confidence: 99%
“…Incentives for not taking responsibility are: a perception of health as being inessential; siblings with serious and chronic diseases that require great attention from their mothers; being the child of a single-parent family, and depressive symptoms. 22 It seems that AN sufferers who do not take responsibility for their participation in treatment will try to gain perceived benefits through their anorexia, namely the attention of others, especially family. The fact that depressive symptoms also create eligibility for hospitalization of AN sufferers makes it difficult to take responsibility for participation in treatment, is also noteworthy.…”
Section: Discussionmentioning
confidence: 99%